Impact of CT Imaging in Emergency Medicine - Abdulkarim Munif Alotaibi, Ibrahim Mohammed Alyahiwi, Saeed Nasser Albathan, Fahad Reja Alharbi, Abdulaziz Ali Al motairi; MOHAMMED HLAL ALOSIMY, Ayman sulaiman Al motairi, Raed Humod Alrowily, AWAD SAKER ALMOTAIRI, Farhan Alhari Alanazi (Journal of International Crisis and Risk Communication Research, 2024)
Advances in imaging technology, particularly multidetector computed tomography (CT), have significantly changed the practice of emergency medicine. CT has become such a valuable tool in emergency clinical settings that it has practically become a standard imaging procedure. However, with the overwhelming proliferation of CT imaging, concerns have been raised regarding patient safety and radiation exposure. In particular, the long-term risk of radiation exposure is of concern, especially in young patients who are likely to undergo repeated and frequent imaging. Recent years have witnessed the advent of advanced CT techniques that can minimize radiation exposure, and this has become the subject of research. This paper explores how CT can be best and most safely used in emergency medicine and the latest techniques implemented to address the associated impacts. The paper also addresses the challenges confronting emergency physicians regarding the present and future use of CT in emergency medicine. (Carpenter et al.2020)